The GCN5-CITED2-PKA signalling module controls hepatic glucose metabolism through a cAMP-induced substrate switch - Mashito Sakai (Nature Portfolio, 2016)
GCN5 inhibits hepatic gluconeogenesis through acetylation of PGC-1α. Here the authors show that GCN5 also activates hepatic gluconeogenesis by acetylating histone H3K9, and that the affinity of GCN5 for its different substrates is regulated via phosphorylation at S275 by PKA in a CITED2-dependent manner.